Sozial- und Siedlungsstruktur - Möglichkeiten und Grenzen ihrer Korrelation - Jaschke, Dieter (ERDKUNDE, 1974)
Social groups or combinations of social groups bring about spatial structures specific to them. Through their basic functional patterns they release processes which manifest themselves in the structural characteristics of the cultural landscape, as in the chain-reaction: Social group factor →basic functional patterns → process → structural characteristic. The influence of the basic functions is limited by the reaction potentials of social groups. Structurally decisive are spatial functions and the processes anociated with them, which are responsible for the functional demands made by social groups on the use of space. If, in any area, the basic patterns of the residential population are the major influence on the dominant spatial functions, there is a tight bundle of linkages between the characteristics of social structure and the form of the cultural landscape. The quality of the linkages can be verified by computational correlation of features of social and settlement structure. If an area lies within the influence of one or more basic functional patterns identified with allochthonous social groups, the social structure of the population should only be taken into account in analysing the cultural landscape to the extent that it operates within this area.